Prevention of infective endocarditis in dental procedures for tetralogy of fallot patients - Ari Rosita Irmawati; Ayulistya Paramita Sutarto (Ikatan Radiologi Kedokteran Gigi Indonesia, 2021)
Objectives: Tetralogy of Fallot (ToF) is a congenital heart defect that is often found in children. Complication that can occur is infective endocarditis caused by bacteria that are often found in the oral cavity. Children with ToF are in a high risk of caries, especially in primary dentition. Preparation of the oral cavity must be done before the cardiac surgery. A proper examination and diagnosis of caries is required in determining the dental treatment to reduce the risk of infective endocarditis. Case Report: A boy aged 4 years, weighing 20 kg came to the pediatric dentistry clinic in Surabaya on a referral from Kediri. The patient had ToF with high caries index and will undergo cardiac corrective surgery. Through a brief anamnesis, it was found that this patient's fingernails and lips easily turn blue (cyanosis) if the patient is in an anxious condition. The panoramic photo shows teeth 51, 52, 54, 61, 62, 74, 84 showing radiolucent images from the enamel to the pulp chamber. Conclusion: Prophylactic antibiotics should be given to ToF patients before procedures involving the gingiva and pulp. Radiographs are needed to help establish the diagnosis and plan treatment. Proper oral and dental care must be taken to prevent the occurrence of infective endocarditis. Errors in determining the diagnosis can lead to errors in the treatment plan and increase the risk of infective endocarditis.